Lemierre syndrome presenting as acute mastoiditis in a 2-year-old girl with congenital dwarfism - Jason B. Fischer; Andrew Prout; R. Alexander Blackwood; Kavita Warrier (MDPI AG, 2015)
Lemierre syndrome is defined by septic thrombophlebitis of the internal jugular vein caused by Fusobacterium. Historically, these infections originate from the oropharynx and typically are seen in older children, adolescents and young adults. More recently, otogenic sources in younger children have been described with increasing frequency. We present a case of a two-year old, who initially developed an otitis media with perforation of the tympanic membrane and went on to develop mastoiditis and non-occlusive thrombosis of the venous sinus and right internal jugular vein. Fusobacterium necrophorum was grown from operative cultures of the mastoid, ensuing computed tomography scan revealed occlusion of the internal jugular vein and the patient was successfully treated with clindamycin, ciprofloxacin and enoxaparin. This case demonstrates the importance of considering Fusobacterium in otogenic infections and the consideration of Lemierre syndrome when F. necrophorum is identified.